Adherence to Azathioprine/6-Mercaptopurine in Children and Adolescents with Inflammatory Bowel Diseases: A Multimethod Study - Mervat M. Alsous; Ahmed F. Hawwa; Cameron Imrie; Andras Szabo; Eman Alefishat; Rana Abu Farha; Mohammad Rwalah; Rob Horne; James C. McElnay (Canadian Journal of Gastroenterology and Hepatology)
Background. Measurement of the degree of adherence is a key element for the evaluation of treatment efficacy and safety; thus, adherence plays an important role in clinical research and practice. The aim of this study was to investigate medication adherence in children with inflammatory bowel disease (IBD) utilizing a multimethod assessment approach. A further aim was to examine factors that can influence adherence within this population. Methods. Medication adherence in 47 children (age range 3 to 17 years) with IBD in three centers in Northern Ireland and Jordan was assessed via subjective (parent and child versions of the Medication Adherence Report Scale (MARS) specific questionnaire) and objective methods, that is, high-performance liquid chromatography (HPLC) determination of the 6-mercaptopurine (6-MP) and azathioprine (AZA) metabolites in packed red blood cell samples taken during a clinic visit. Beliefs about prescribed medicines were also assessed in parents/guardians using the Beliefs about Medicines Questionnaire (BMQ). Results. An overall nonadherence to AZA/6-MP therapy in children with IBD was found to be 36.17% (17 out of 47 patients were classified as nonadherent using at least one of the assessment methods). A total of 41 patients (91.1%) were classified as adherent to AZA or 6-MP using the blood sampling, while adherence rates using the MARS questionnaire completed by children and parents/guardians were 60.6% and 72.7%, respectively. The latter provides a more longitudinal measure of adherence. Child self-reported nonadherence rates were significantly higher than parent/guardian reported rates (p=0.013). Binary logistic regression analysis identified age to be independently predictive of adherence, with adolescents (children aged ≥ 13 years old) more likely to be classified as nonadherent. Regarding the BMQ, when parental/guardian necessity beliefs outweighed concerns, that is, higher scores in the necessity-concern differential (NCD), adolescents were more likely to be classified as adherent. Conclusion. Results provide evidence for ongoing adherence challenges in the paediatric population with IBD. It is recommended that parents/guardians (particularly of older children) and older children themselves, should receive enhanced counselling and education about their prescribed medicines.